A Translation Shift Analysis On Verb And Verb Phrase OfThe Avengers Movie And Its Subtitling - Setyaningsih, Setyaningsih, Dra. Dwi Haryanti, M.Hum, Dr. Anam Sutopo, M.Hum (2013)
The objective of this research are categorizing the translation shift and the markers of translation shifts of verb and verb phrase as well as portraying the equivalence of verb and verb phrase which is found in the Avengers movie and its subtitling. This type of this research is descriptive qualitative. The data are sentences contain verb and verb phrase which have shift. She uses documentation in collecting data and comparing both English and Indonesian subtitling in analyzing data. The result of this research shows that first, there are 26 types of translation shift of verb and verb phrase, i.e. First, from 445 data, there are 14 data or 1,44% belong to category shift and 12 data or 1,23% belong to level shift of verb and verb phrase. Then, the markers of translation shift, there are seven markers in SL and eleven markers in TL. Firstly, The markers in SL are auxiliary (such as should, can, will, do, does, did, has, have, could, would, ought to and have to), suffix (such as -s, -es, -ed), conjunction (i.e. but), preposition (i.e. to), be + V-ing (such as is, was, were), be + V3 (such as is) and is + gonna +V1. Secondly, the markers in TL, i.e. conjunction (like yang, selain), negation (i.e. tidak), tense (akan, bisa, sedang), perfect (i.e. belum, sudah), quality (like terlalu, lebih), a must (harus), prefix (like ber-, me-, ter-, di-), suffix ( -an, -i. -kan), affix (pengan, me-kan, meng-i, ke-an, me-i, di-kan, se-nya, ber -lah), and particle -lah. Second, there are 397 data or 89,21% belong to equivalent translation and 48 data or 10,79% belong to non-equivalent translation.